Epidemiology of the association between serum 25-hydroxyvitamin D levels and musculoskeletal conditions among elderly individuals: a literature review - Kazuhiko Arima; Satoshi Mizukami; Takayuki Nishimura; Yoshihito Tomita; Hiroki Nakashima; Yasuyo Abe; Kiyoshi Aoyagi (Journal of Physiological Anthropology, 2020)
Abstract Background Vitamin D deficiency is associated with osteoporosis, fracture, muscle weakness, falls, and osteoarthritis in adults. Elderly individuals are more likely to present with poor musculoskeletal conditions. Recently, several epidemiological studies have assessed the correlation between serum 25-hydroxyvitamin D (25(OH)D) levels and musculoskeletal conditions in elderly individuals. Main text Osteoporosis is a skeletal disease characterized by low bone mass and microarchitectural deterioration of bone tissue, with a consequent increase in bone fragility and susceptibility to fracture. Numerous studies have shown a positive association between serum 25(OH)D levels and bone mineral density. Only a few studies have reported an association between serum 25(OH)D levels and quantitative ultrasound (QUS) parameters. Low serum 25(OH)D level may be a risk factor for hip fracture. However, data on the association between vitamin D deficiency and the incidence of non-hip fracture are contrasting. Falls are a major cause of mortality and morbidity in older adults. Several prospective population-based cohort studies have shown that low 25(OH)D levels are associated with an increased risk of falls. Reduced muscle strength and physical performance are risk factors for adverse events, including disability, institutionalization, and mortality. The role of vitamin D in musculoskeletal functionality (muscle weakness and physical performance) among elderly individuals is still controversial. Osteoarthritis (OA) is the most common form of arthritis and is a leading cause of disability among older adults. Data on the association between serum 25(OH)D levels and OA are contrasting. Conclusion Some studies have shown that vitamin D deficiency may be a risk factor for poor musculoskeletal conditions, such as osteoporosis, fracture, muscle weakness, falls, and osteoarthritis in adults. However, other studies did not find an association between serum 25(OH)D levels and musculoskeletal conditions.